Egocentric and allocentric spatial reference frames in aging: A systematic review. (September 2017) - Colombo, Desirée; Serino, Silvia; Tuena, Cosimo; Pedroli, Elisa; Dakanalis, Antonios; Cipresso, Pietro; Riva, Giuseppe
Highlights: Aging does not affect egocentric navigational strategies, whereas allocentric and switching abilities show a gradual decline. A general age-related weakening of spatial memory has been observed, even if not frame-specific;. Executive functions may play a critical role in age-related spatial difficulties. Abstract: Aging affects many aspects of everyday living, such as autonomy, security and quality of life. Among all, spatial memory and spatial navigation show a gradual but noticeable decline, as a result of both neurobiological changes and the general slowing down of cognitive functioning. We conducted a systematic review using the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines to identify studies that specifically investigated the role of allocentric and egocentric frames in healthy aging. Concerning spatial navigation, our results showed a preservation of egocentric strategies, along with specific impairments in the use of allocentric and switching abilities. Regarding spatial memory, instead, outcomes were more divergent and not frame-specific. With this perspective, spatial impairments were discussed considering the cognitive profile of mild cognitive impairment (MCI) and Alzheimer's Disease (AD).